Financial Literacy, Debt Burden and Impulsivity: A Mediation Analysis. (7th December 2017) - Ottaviani, Cristina; Vandone, Daniela
Abstract : After the 2008 crisis, EU regulatory authorities and policy makers started to devote resources to improve households' financial literacy, considered as a key element of debt decisions. However, the role of another crucial determinant of debt burden has been neglected in such financial education programmes. The present study examines the role of impulsivity and financial literacy as predictors of debt burden in a sample of 445 individuals. An ad‐hoc built indicator of financial literacy and scores on the Barratt Impulsiveness Scale were used as regressors. The debt service to income ratio, a proxy of debt burden, served as the dependent variable. Both predictors resulted associated with debt burden; however, impulsivity fully mediated the impact of financial literacy on debt, even after controlling for financial wealth. Findings are discussed in terms of policy implications and means to formulate more effective financial education programmes.